Learners' Perceptions During Simulation-Based Training: An Interview Study Comparing Remote Versus Locally Facilitated Simulation-Based Training. Issue 5 (October 2018) - Duch Christensen, Margrethe; Oestergaard, Doris; Dieckmann, Peter; Watterson, Leonie
Abstract : Introduction: Remotely facilitated simulation-based training (RF-SBT) is less positively appraised than face-to-face, locally facilitated simulation-based training (LF-SBT), despite being considered as an acceptable alternative. This study compared the perceptions of learners after RF-SBT and LF-SBT to explain differences between the two and identify relevant theories that would guide future practice. Methods: Telephone interviews were conducted with 21 newly graduated doctors and nurses who completed a standardized simulation course delivered in both RF-SBT and LF-SBT formats. Results: Participants reported that both SBT formats to be highly beneficial, however, were less positive about RF-SBT. They described a range of psychosocial and cognitive responses that explained their positive and negative attitudes to different aspects of the training. These perceptions, occurring across both formats, included a sense of the following: belonging to instructor and group, surveillance, responsibility, realism, contextual understanding, conscious mental effort, control of attention, and engagement with task. Participants associated these perceptions and ensuing attitudes to SBT with factors arising during, and/or existing before, the SBT as if in an input-output process model. The former 'enabling' factors related to human interaction, technology, and instructional design, whereas the latter 'precursor' factors reflected pre-existing attributes of the participants and instructors. These findings are supported by several theoretical models of which the technology acceptance model is arguably the best fit. Conclusions: Locally facilitated simulation-based training is easier to use and experience than RF-SBT; however, the latter's negative impact may be concealed by SBT's overarching very high perceived value. The technology acceptance model is an appropriate conceptual model to explain these processes. Abstract : Supplemental digital content is available in the text.